Immunophenotypic and molecular profile of cancer stem-cell markers in ex vivo canine transmissible venereal tumour (CTVT) - Grandi, Fabrizio [UNESP]; Miot, Helio Amante [UNESP]; Rocha, Rafael Malagoli; Gomes, Cristina Massoco Salles; Queiroz-Hazarbassanov, Nicolle; Montoya-Florez, Luis Mauricio; Cogliati, Bruno; Rocha, Noeme Sousa [UNESP] (Wiley-Blackwell, 2022)
Background: Several studies have attempted to characterise the origin of canine transmissible venereal tumour (CTVT). However, the participation of cancer stem cells (CSC) has not been reported Objectives: Herein we describe the expression patterns of CSC markers CD44, CD34, CD90 and CD133 in CTVT Methods: Thirty-eight samples were selected and assessed through flow cytometry and immunohistochemistry Results and conclusions: Twenty-two tumours were classified as plasmacytoid and 16 as mixed. Almost all tumours showed high CD44 and low CD34 levels. CD133 and CD 90 expression varied among tumours. Cytological groups did not differ in the proportion of CSC markers. Our results suggest that CSC subpopulations might participate in CTVT.
Keywords: Dog; flow cytometry; Immunohistochemistry; Lyrnphocytoid